The Cells and Extracellular Matrix of Human Amniotic Membrane Hinder the Growth and Invasive Potential of Bladder Urothelial Cancer Cells - Ramuta, Taja Železnik; Jerman, Urška Dragin; Tratnjek, Larisa; Janev, Aleksandar; Magatti, Marta; Vertua, Elsa; Bonassi Signoroni, Patrizia; Silini, Antonietta Rosa; Parolini, Ornella; Kreft, Mateja Erdani (Frontiers in Bioengineering and Biotechnology, 2020)
Bladder cancer is one of the most common cancers among men in industrialized countries and on the global level incidence and mortality rates are increasing. In spite of progress in surgical treatment and chemotherapy, the prognosis remains poor for patients with muscle-invasive bladder cancer. Therefore, there is a great need for the development of novel therapeutic approaches. The human amniotic membrane (hAM) is a multi-layered membrane that comprises the innermost part of the placenta. It has unique properties that make it suitable for clinical use, such as the ability to promote wound healing and decrease scarring, low immunogenicity, and immunomodulatory, antimicrobial and anticancer properties. This study aimed to investigate the effect of (i) hAM-derived cells and (ii) hAM scaffolds on the growth dynamics, proliferation rate, and invasive potential of muscle-invasive bladder cancer T24 cells. Our results show that 24 and 48 h of co-culturing T24 cells with hAM-derived cells (at 1:1 and 1:4 ratios) diminished the proliferation rate of T24 cells. Furthermore, when seeded on hAM scaffolds, namely (1) epithelium of hAM (e-hAM), (2) basal lamina of hAM (denuded; d-hAM), and (3) stroma of hAM (s-hAM), the growth dynamic of T24 cells was altered and proliferation was reduced, even more so by the e-hAM scaffolds. Importantly, despite their muscle-invasive potential, the T24 cells did not disrupt the basal lamina of hAM scaffolds. Furthermore, we observed a decrease in the expression of epithelial-mesenchymal transition (EMT) markers N-cadherin, Snail and Slug in T24 cells grown on hAM scaffolds and individual T24 cells even expressed epithelial markers E-cadherin and occludin. Our study brings new knowledge on basic mechanisms of hAM affecting bladder carcinogenesis and the results serve as a good foundation for further research into the potential of hAM-derived cells and the hAM extracellular matrix to serve as a novel bladder cancer treatment.